Gênero, espacialidade e sustentabilidade: as mulheres chefes de família do Parque Residencial Manaus – Prosamim. - (:unkn) unknown (Universidade Federal do Amazonas, 2014)
The research is exploratory and presents quantitative qualitative nature, once that it proposes to know the socioeconomic profile of the female households, as well as the perceptions of their reality. The results of this research will provide a glimpse into the daily lives of these women showing their work and life conditions.The aim of the research is to develop a study about the sustainability and citizenship levels of the female households from the Residential Park Manaus - I PROSAMIM based in the integrated analysis of three approache levels: gender, spatiality and sustainability. The methodological procedures were varied, bibliographical, documentary, participatory and field research. Lastly, the writing results analysis with graphing from primary and secondary information. According to IBGE 2012, the statistics show that is concentrated in Manaus, more than half of Amazonas state population. From 3, 590, 985 inhabitants of this state, 1, 861, 863 live in the capital, representing a rate of 51.84% (IBGE, 2012). This people concentration in urban areas is a common situation in all states of the Federation, and it is associated to the process issues of mobility population between the countryside and the city. Data from Residencial Park Manaus expressed that householders are mostly women and support the dependents salary range that sets up R$ 240.00 to R$ 720.00, as it corresponds to 64.3% of the interviewed families. According to the collected and analyzed data it became evident that public housing politics which aim to mitigate existing inequalities in urban areas should include actions that go beyond the acquisition of a home,it is also necessary to take measures to provide access to urban equipment and services from the specifications and peculiarities of each social agent. It was concluded that female households live outside of the sustainability premises in Manaus.
Keywords: Gênero; Espacialidade; Sustentabilidade; Mulheres; Prosamim; Sustainability; Spatiality; CIÊNCIAS HUMANAS: GEOGRAFIA